Subject age in P300 BCI - Dias, N. S. (2005)
This paper presents a study about the amplitude, latency and distribution of P300 in twelve healthy volunteers (5 women and 7 men, aged between 19-70, with a mean of 35.5 years) that were submitted to two Novelty Oddball Paradigms. The difference between them is on stimulus modalities, which are visual and auditory. Usually, a P300-based brain computer interface has visual stimuli but we are also interested in making analogies between the two modalities. In both test modalities were presented 3 types of stimuli: a ‘standard’ stimulus, a ‘target’ stimulus, to which the subject must respond, and a ‘novel’ stimulus. Most of the subjects were students and are naive to the purposes of the experiment. The subject is not warned about the ‘novel’. We recorded scalp potentials from 18 channels distributed in a standard configuration 10-20 system. Target P300 had more relevance than novel P300 for a BCI application. Results show relevant differences in amplitude and latency in P300 signal for different ages. The Older subjects (>51 years) show smaller P300 amplitudes than younger. Therefore, the subject age must be taken into account when a P300 BCI application is implemented.